Cost-efficient entrapment of β-glucosidase in nanoscale latex and silicone polymeric thin films for use as stable biocatalysts. (1st January 2016) - Javed, Muhammad Rizwan; Buthe, Andreas; Rashid, Muhammad Hamid; Wang, Ping
Highlights: Novel latex and silicone polymeric thin films for β-glucosidase immobilization have been reported. Latex showed highest apparent activity while the entrapment efficiency was highest for silicone. The entrapment resulted in the thermo-stabilization of the β-glucosidase. Immobilized β-glucosidase significantly increased the cellulosic substrate hydrolysis rate. Functional stability and reusability of the immobilized β-glucosidase was also quite high. Abstract: β-Glucosidase is an ubiquitous enzyme which has enormous biotechnological applications. Its deficiency in natural enzyme preparations is often overcome by exogenous supplementation, which further increases the enzyme utilization cost. Enzyme immobilization offers a potential solution through enzyme recycling and easy recovery. In the present work Aspergillus niger β-glucosidase is immobilized within nanoscale polymeric materials (polyurethane, latex and silicone), through entrapment, and subsequently coated onto a fibrous support. Highest apparent activity (90 U g −1 polymer) was observed with latex, while highest entrapment efficiency (93%) was observed for the silicone matrix. Immobilization resulted in the thermo-stabilization of the β-glucosidase with an increase in optimum temperature and activation energy for cellobiose hydrolysis. Supplementation to cellulases also resulted in an increased cellulose hydrolysis, while retaining more than 70% functional stability. Hence, the current study describes novel preparations of immobilized β-glucosidase as highly stable and active catalysts for industrial food- and bio-processing applications.